Speech‐language performance and comorbid disorders in children with perisylvian syndrome induced by viral encephalitis - Dianrong Sun; Jianhui Zhao; Leihong Zhang; Rong Yu; Mei Hou (Pediatric Investigation, 2024)
ABSTRACT Importance Viral encephalitis is one of the main causes of the perisylvian syndrome, which can cause damage to children's language‐speech, feeding, and swallowing functions. Comprehensive assessment of language‐speech and swallowing function and comorbidity research on these children will help children's rehabilitation workers to better understand the disease and strengthen the systematic management of comorbid disorders. Objective To describe speech and language pathology and the occurrence of comorbid disorders in children with perisylvian syndrome induced by viral encephalitis. Methods Twenty‐two children with acquired perisylvian syndrome were recruited in this study. Language and speech functions, including oral motor function, swallowing function, language ability, and dysarthria were assessed in these patients. Craniocerebral magnetic resonance imaging (MRI), electroencephalogram examination, and intelligence evaluation were performed to determine brain lesions and comorbid disorders. Results All children exhibited different degrees of oral movement, dysphagia, and speech and language disorders. There was a significant difference between expressive and receptive language ability (P < 0.05). There were 10, 8, and 12 children who had an intellectual disability, limb disability, and epilepsy, respectively. In addition to the damage of the peri‐tegmental cortex found in MRI, thalamus lesions occurred in 19 cases and white matter involvement in six cases. Interpretation Children with acquired perisylvian syndrome caused by viral encephalitis are characterized by persistent pseudobulbar dysfunction, speech and language impairment, and orofacial diplegia. They have a high probability of secondary epilepsy and are prone to motor and cognitive impairment, which need systematic management.